Analysis of production and growth of three varieties of spinach (Amaranthus spp L.) on AB Mix nutrition concentration in DFT (Deep Flow Technique) hydroponic system - Arisandi, Nadila; Oesman, Roswita; Harahap, Lutfi Henderlan (Contributions of Central Research Institute for Agriculture, 2024)
This study aims to determine the appropriate concentration of AB Mix for the growth of three varieties of spinach (Amaranthus spp. L.) in DFT hydroponic system. The parameters observed were plant height (cm), number of leaves (strands), root length (cm), fresh weight of the whole plant at harvest (g) and fresh weight of the consumed plant (g). The research will begin in July-August 2023. The research used hydroponic technique with DFT (Deep Flow Technique) system using BA202 green spinach, Mira red spinach, and BA132 red spinach seeds. The research was conducted using the Completely Randomized Design (CRD) method consisting of one treatment factor and applied to three spinach varieties namely green spinach (V1), red spinach (V2), mira spinach (V3) and repeated 3 times. The treatment factor is the addition of AB Mix (AB) nutrient concentration which consists of 3 levels, namely: AB1 = Addition of AB Mix 900 ppm, AB2 = Addition of AB Mix 1,100 ppm, AB3 = Addition of AB Mix 1,300 ppm. The research was conducted in the greenhouse of the Faculty of Agriculture, National Development University "Veteran" of East Java Medan. Based on Statistical Test and Analysis of Variance, the results showed that the effect of different varieties had a significant effect with the value of F count > F table on plant height, number of leaves, fresh weight of the whole plant at harvest and fresh weight of plants consumed but had no significant effect with the value of F count < F table on plant height (cm) on root length.